Konceptframtagning av kylutrustning till ett litiumbatteri - Karlsson, Martin; Nilsson Bornhall, Gustav (My University, 2019)
Abstract In this report, which is written for Chalmers university of technology and on behalf of Semcon, it is evaluated how to design and integrate a cooling equipment for one of the battery company’s products. The battery company specialize in flexible lithium battery technology, they offer high performance battery solutions, based on the customer needs. When these batteries are put to use, the amount of stored energy decrease, which means that the user is required to charge the battery. This charging operation is performed by adding power to the battery cells, which result in heat being generated. The heat generated consists of resistive heating and heat generated by the chemical reaction within the battery cell. The battery company wants to reduce the charging time by enabling fast charging. Fast charging a battery means that the amount of added power per unit time is increased. The increased amount of power being added result in higher temperature levels in the battery cells and the risk of reaching critical temperatures is also higher. By reaching these critical temperatures the charging rate gets less efficient due to the batteries regulating BMSsystem, the battery cells performance and lifetime is also affected in a negative way. To solve this problem and make fast charging possible, a cooling equipment is required. Based on the thesis background the purpose is to develop a cooling equipment, customized to cool a lithium battery and therefore minimize the charging time based on the reduced temperature within the module. The development of a whole cooling system with components like: pump, hoses, connections and heat exchanger, is not included in this report. The project started by performing a wide range information retrieval about the main parameters that affect different types of cooling methods with liquid as coolant. The concept generation is based on the information that was obtained through the information retrieval.. The main result of the thesis work is the final concept that answers to the question “how can a cooling equipment be designed to cool the company’s lithium batteries without making any changes to the current battery modules design”. The final concept consists of a copper cooling block with internal channels and its coolant lines with a water glycol solution as coolant. A thin electric insulating film is placed between the cooling equipment and the component that transfers the current in the module to reduce the risk of shorting the battery cells. The final concept can be integrated in the battery module without making any major changes, this has been confirmed by a CAD-program. The dimensioning of the final concept is based on existing products and assumptions, thereby it can be stated that the concept will minimize the charging time and limit the heat generated.
Keywords: Produktion; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Production; Innovation & Entrepreneurship; Mechanical Engineering